Biomechanical tools to study dental implants: A literature review - Tribst, João Paulo Mendes (2016)
Since 1980, the biomechanical behavior of dental implants has received importance regarding the issue of failure in this rehabilitation system due to occlusal overload. Through bioengineering tools, several studies have been conducted to answer about the influence of different factors on the biological response. Bioengineering tools such as finite element analysis (FEA), strain gauge (SGA), photoelasticity (PEA) and digital image correlation (DIC) are widely inspiring clinical extrapolation of possible solutions in the mechanics of implantology. This study has aimed to investigate the available stress analysis methods to study dental implants’ behavior through a literature review. This review started with a PubMed search from the mostly old studies of each methodology correlated to biomechanical behavior of dental implants used with dental implants studies until 2016. FEA, SGA, PEA and DIC methodologies are capable to elucidate the mechanical behavior of this rehabilitation system. However, the combination of two or more methods gives more detailed explanation and avoids limitations of a single methodology.